Basic understanding of capital market operation - Ekiran, Oba (Lagos, Nigeria CIBN Press Limited, 1999)
This book is written with the diagrammatic illustrations to assist readers to have the required basic understanding of the capital market in terms of what the market is, the players and the commodities that are sold, the capital market functionaries and operations; regulation and miscellaneous subjects and the need for market redefinitions.
Loan
nmn, 26/07/16
Keywords: Capital market; Capital market operations